Knowledge, attitude and practice of Malawian farmers on pre- and post-harvest crop management to mitigate aflatoxin contamination in groundnut, maize and sorghum: Implication for behavioral change - Anitha, Seetha; Tsusaka, Takuji W.; Njoroge, Samuel; Kumwenda, Nelson; Botha, Rosemary (MDPI, 2019)
A knowledge, attitude and practice (KAP) study was conducted in three districts of Malawi to test whether the training had resulted in increased knowledge and adoption of recommended pre- and post-harvest crop management practices, and their contribution to reducing aflatoxin contamination in groundnut, maize and sorghum. The study was conducted with 900 farmers at the baseline and 624 farmers at the end-line, while 726 and 696 harvested crop samples were collected for aflatoxin testing at the baseline and end-line, respectively. Results show that the knowledge and practice of pre- and post-harvest crop management for mitigating aflatoxin were inadequate among the farmers at the baseline but somewhat improved after the training as shown at the end-line. As a result, despite unfavorable weather, the mean aflatoxin contamination level in their grain samples decreased from 83.6 to 55.8 ppb (p < 0.001). However, it was also noted that increased knowledge did not significantly change farmers’ attitude toward not consuming grade-outs because of economic incentive incompatibility, leaving potential for improving the practices further. This existing gap in the adoption of aflatoxin mitigation practices calls for approaches that take into account farmers’ needs and incentives to attain sustainable behavioral change.